Profiling immunity to HIV vaccines with systems biology - Andersen-Nissen, Erica (2012)
PURPOSE OF REVIEW: The recent modest success of the RV144 HIV vaccine trial in Thailand has shown that development of an HIV vaccine is possible. Designing a vaccine that achieves better protection, however, will require a more complete understanding of vaccine mechanisms of action and correlates of protection. Systems biology approaches enable integration of large datasets from a variety of assays and offer new approaches to understanding how vaccine-induced immune responses are coordinately regulated. In this review, we discuss recent advances in clinical trial design, specimen collection, and assay standardization that will generate datasets for systems analyses of immune responses to HIV vaccines. RECENT FINDINGS: Several recently-published HIV vaccine trials have shown that different HIV vaccine prime/boost combinations can greatly affect the immune response generated, but mechanistic insights into their modes of action are lacking. Novel systems biology studies of efficacious, licensed vaccines provide a new template for analysis of HIV vaccines. To generate datasets appropriate for systems analysis, current HIV vaccine clinical trials are undergoing design modifications and increased standardization of specimen collection and immune response assays. SUMMARY: Systems biology approaches to HIV vaccine evaluation are driving new methods of HIV vaccine immune response profiling in clinical trials, and will hopefully lead to new improved HIV vaccines in the near future.